Students’ Opportunities, Challenges and Coping Mechanisms in Limited Face-To-Face Classes in Eastern Samar State University, Philippines - Lapada, Aris Alea (Jurnal Pendidikan Progresif, 2023)
Students’ Opportunities, Challenges and Coping Mechanisms in Limited Face-To-Face Classes. Objectives: This study aimed to determine the students’ opportunities, challenges and coping mechanisms in limited face-to-face classes at the College of Education, Eastern Samar State University. A phenomenological study was employed to gather qualitative data from the participants. For the second semester, the school year 2021 - 2022, students from the first-year level to third-year level had limited face-to-face-learning. Half of the 54-hour lectures of every course were recited through a distance learning approach, while the remaining 27 hours were recited through face-to-face encounters in the college. Methods: A total of 74 students agreed to participate in the study. They had to make a weekly journal log to determine the challenges and opportunities in limited face-to-face classes. Moreover, Six focus group discussions with three randomly chosen students were also done as another data source. Findings: Among the students’ learning opportunities were in-depth conceptual understanding, self-paced learning, self-regulated learning, and prompt teachers’ feedback. On the other hand, the learning challenges encountered by the students were internet connectivity glitches and course design issues. From the challenges identified by the students, relocating to other places with good internet speed and asking for help from classmates were their coping mechanisms for internet connectivity glitches, while asking for help from classmates and understanding the issues through peer support were students’ coping mechanisms for course design issues. Conclusion: The students’ opportunities of limited face-to-face classes led them to succeed in their academic performance; moreover, they could cope with all the challenges they faced during the limited face-to-face classes.   Keywords: limited face-to-face classes, opportunities, challenges, coping mechanism.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202335